Valve-in-valve procedure after CoreValve pop-out - Gasecka, Aleksandra; Kotulecki, Aleksander; Gałuszka, Kacper; Huczek, Zenon; Ścisło, Piotr; Rymuza, Bartosz; Kochman, Janusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Aortic stenosis (AS) is one of the most common valvular pathologies in the developed countries. Transcatheter aortic valve implantation (TAVI) has become an accepted treatment for severe AS in high and intermediate risk patients, as an alternative to surgical aortic valve replacement (SAVR) [1]. Although TAVI is a less invasive procedure than SAVR, it carries a risk of complications including valve misplacement or embolization [2].